2015
DOI: 10.3390/nu7125533
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Health Labels on Flavor Perception and Emotional Profiling: A Consumer Study on Cheese

Abstract: The global increase of cardiovascular diseases is linked to the shift towards unbalanced diets with increasing salt and fat intake. This has led to a growing consumers’ interest in more balanced food products, which explains the growing number of health-related claims on food products (e.g., “low in salt” or “light”). Based on a within-subjects design, consumers (n = 129) evaluated the same cheese product with different labels. Participants rated liking, saltiness and fat flavor intensity before and after cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
44
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(55 citation statements)
references
References 98 publications
(131 reference statements)
9
44
0
2
Order By: Relevance
“…These results also support the growing body of literature stating that emotional conceptualizations are mainly sensory driven (Gibson, ; Gutjar et al, ; King & Meiselman, ; Ng et al, ; Schouteten et al, ; Schouteten et al, ; Spinelli et al, ; Thomson, Crocker, & Marketo, ). For instance, while a large part of the children and teenagers associated positive emotions with the local producer logo (logo condition), the number of participants checking the same positive emotions is substantially lower during the informed condition, but similar to the number of participants in the blind condition.…”
Section: Discussionsupporting
confidence: 85%
“…These results also support the growing body of literature stating that emotional conceptualizations are mainly sensory driven (Gibson, ; Gutjar et al, ; King & Meiselman, ; Ng et al, ; Schouteten et al, ; Schouteten et al, ; Spinelli et al, ; Thomson, Crocker, & Marketo, ). For instance, while a large part of the children and teenagers associated positive emotions with the local producer logo (logo condition), the number of participants checking the same positive emotions is substantially lower during the informed condition, but similar to the number of participants in the blind condition.…”
Section: Discussionsupporting
confidence: 85%
“…Various surveys on consumers’ attitudes, acceptance or purchase intention of GM (De Steur et al, ; Grunert, Bech‐Larsen, Lähteenmäki, Ueland, & Åström, ; Lähteenmäki et al, ; Magnusson & Koivisto Hursti, ) or GM‐free (labelled) food (Tsourgiannis et al, ) have highlighted the importance of taste. Labelling itself, however, could also have an impact on sensory perceptions (Litt & Shiv, ; Piqueras‐Fiszman & Spence, ), as shown for various credence attributes, such as brand (Paasovaara, Luomala, Pohjanheimo, & Sandell, ) or content information (Stefani, Romano, & Cavicchi, ; Torres‐Moreno, Tarrega, Torrescasana, & Blanch, ), and environmental (Lee, Shimizu, Kniffin, & Wansink, ) or health claims (Schouteten et al, ; Wansink, Park, Sonka, & Morganosky, ). Credence attributes are labels or other types of information, such as nutritional value, production methods (e.g., GM technology) or origin, which provide credibility of the seller in relation to the buyer, although this cannot be verified by consumers due to their lack of technical expertise or practical possibilities even after consumption (Fernqvist & Ekelund, ).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding package information, recent studies have demonstrated its impact on the emotional conceptualisations consumers experience when evaluating a food product (Gutjar et al, ; Ng, Chaya, & Hort, ; Spinelli, Masi, Zoboli, Prescott, & Monteleone, ). But also more specific information related to the content or health claims has shown to affect consumers’ emotional or sensory profiles of food products (Schouteten et al, 2015a; 2016, Wansink & Park, 2002). As such, and given the controversy of GM technology (Lusk et al, ), it is useful to include an emotional assessment when evaluating sensory perceptions of GM‐food related labelling.…”
Section: Introductionmentioning
confidence: 99%
“…That is, the taste profile of S1.5PL, which had the same taste profile as that of S2.0, may not have fit well to what consumers expected for “sodium‐reduced kimchi with 25% of salt (sodium) reduction by using salt replacer,” especially in terms of saltiness intensity. Previous studies have shown that providing information about sodium reduction significantly reduced the expected level of saltiness in chicken soup (Liem et al., ) and cheese (Schouteten et al., ). Similar to that perspective, despite the healthiness perception of the control kimchi being the lowest among all the labels provided, consumers liked the control sample the most along with S1.5, probably because the taste profile of S2.0 fit the expected profile of “general kimchi.”…”
Section: Discussionmentioning
confidence: 96%